Angiopoietin 2 displays a vascular endothelial growth factor dependent synergistic effect in hepatocellular carcinoma development in mice. Issue 12 (20th July 2005) - Yoshiji, H; Kuriyama, S; Noguchi, R; Yoshii, J; Ikenaka, Y; Yanase, K; Namisaki, T; Kitade, M; Uemura, M; Masaki, T; Fukui, H
Abstract : Background: Orchestration of two major classes of angiogenic factors—namely, vascular endothelial growth factor (VEGF) and angiopoietin 2 (Ang-2)—has been shown to play a pivotal role in tumour angiogenesis, including hepatocellular carcinoma (HCC). However, few studies have focused on the direct interaction of these factors on in vivo tumour development and angiogenesis. Aim: To examine the interaction between both factors in murine HCC. Methods: We examined the combination effect of VEGF and Ang-2 overexpression by means of a combination of a retroviral tetracycline (tet) regulated gene manipulating system in vivo, by providing tet in the drinking water, and a conventional plasmid gene expression system. Results: Neither Ang-2 nor VEGF overexpression induced proliferation of HCC cells in vitro. In vivo, although overexpression of Ang-2 did not increase tumour development, simultaneous expression of Ang-2 and VEGF synergistically augmented tumour growth and angiogenesis in murine HCC. Ang-2 plus VEGF induced tumour development was markedly attenuated by treatment with neutralising monoclonal antibodies against VEGF receptors. Ang-2 plus VEGF overexpression significantly increased the activities of matrix metalloproteinase (MMP)-2 and MMP-9 in the tumour. Suppression of intratumoral VEGF almost completely abolished this augmentation of MMPs. Conclusions: These results suggest that Ang-2 synergistically augments VEGF mediated HCC development and angiogenesis. This proangiogenic activity was exerted only in the presence of VEGF, at least partly mediated via induction of MMP-2 and MMP-9 in the tumour.